Lipid membranes accelerate amyloid formation in the mouse model of AA amyloidosis. (2nd January 2019) - Vahdat shariat panahi, Aida; Hultman, Per; Öllinger, Karin; Westermark, Gunilla T.; Lundmark, Katarzyna
Abstract: Introduction: AA amyloidosis develops as a result of prolonged inflammation and is characterized by deposits of N-terminal proteolytic fragments of the acute phase reactant serum amyloid A (SAA). Macrophages are usually found adjacent to amyloid, suggesting their involvement in the formation and/or degradation of the amyloid fibrils. Furthermore, accumulating evidence suggests that lipid membranes accelerate the fibrillation of different amyloid proteins. Methods: Using an experimental mouse model of AA amyloidosis, we compared the amyloidogenic effect of liposomes and/or amyloid-enhancing factor (AEF). Inflammation was induced by subcutaneous injection of silver nitrate followed by intravenous injection of liposomes and/or AEF to accelerate amyloid formation. Results: We showed that liposomes accelerate amyloid formation in inflamed mice, but the amyloidogenic effect of liposomes was weaker compared with AEF. Regardless of the induction method, amyloid deposits were mainly found in the marginal zones of the spleen and coincided with the depletion of marginal zone macrophages, while red pulp macrophages and metallophilic marginal zone macrophages proved insensitive to amyloid deposition. Conclusions: We conclude that increased intracellular lipid content facilitates AA amyloid fibril formation and show that the mouse model of AA amyloidosis is a suitable system for further mechanistic studies.